Fluctuations in epistemic (a)symmetry in video-mediated post-observation conversations - Topal, Pınar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
Evidence-based reflective practices are promoted in all recent frameworks for language teacher education (LTE). However, the research into how the mentor and trainees sequentially and relationally orient to these data-led sequences remains scarce. Similarly, video-mediated pedagogical interactions need to move forward from the first aid approach to have a sustainable understanding of the video-mediated LTE. With this in mind, this thesis primarily investigates epistemic asymmetries unfolding in video-mediated post-observation conversations (POC) in language teaching practicum. The video-recordings of 17 video-mediated POCs are micro analysed using the theoretical and methodological tenets of multimodal conversation analysis. Data suggests that the fluctuations in epistemic (a)symmetry serve as a catalyst for the progression of reflection and evaluation-oriented sequences. That is, the mentors strategically downgrade their epistemic position to index the trainees’ experiential knowledge and invite for reflection. However, the tide turns when the mentors initiate evaluation-oriented sequences in which the volume of trainee voice is turned down. They systematically insert their epistemic authority to limit any potential resistance that would challenge their epistemic, as well as deontic authority to do evaluation. The video medium also creates unique multimodal opportunities for mutual orientation to evidence. The findings are conducive to the expanding research into the affordances and challenges of video-mediated language teacher education and have possible pedagogical and research implications for our understanding of the sequential and relational organization of epistemics in feedback conversations.
Keywords: English teachers -- Training of.